Chimera Anamnesis tackling the lack of Philippine science fiction novels - Hernandez, Maria Christina Cecelia, C. (College of Arts and Letters, University of the Philippines Diliman, 2013)
The Philippines currently lacks well-written science fiction novels which bring Philippine mythology to the present day. Most of our speculative fiction works are short fiction and comics, to be found in various anthologies. Magic in our fiction has been worn thin. My essay surveys Philippine fiction which brings mythology to he present day, and foreign literature that does so using science fiction, in order to see what has been done and what techniques can be used to bring our diverse and unqique Philippine mythology to the present day setting in a science fiction novel. My creative work is a science fiction novel, set in the Philippines with a range of Filipino characters, which brings creatures of Philippine mythology to the present day. Many chapters were originally written as short stories of flash fiction, but have been adapted to better fit the long form.